Global trend of science and religion in educational research from 2015 to 2024: a scoping review - Zulfah; Edy Cahyono; Sutikno Madnasri; Dyah Rini Indriyanti; Saiful Ridlo; Effendi Effendi (EDUSAINS, 2025)
The history of the relationship between science and religion in education provides diverse dynamics; in recent years, the two have begun to be integrated constructively, including in the field of education, especially in natural sciences learning. This scoping review aims to identify the research trends in the natural sciences related to religion, including the contributions of the author's country, the topic of science learning, the area of religion, and the teaching methods used. Teaching methods are essential to present science and religion in the classroom. Documents were taken from data bases indexed by Scopus, ERIC, and WOS, with a total of 1844 from 2015 to 2024, which were then filtered into 55 documents by adapting the PRISMA method.  The scoping review method is carried out by analyzing the content of each article. The analysis results show that the author's contributions to science and religion research in education are most significant in the UK, the US, and Indonesia. At the same time, this topic talks a lot about biology topics, especially evolutionary material in the area of Christianity. A method that is often used in teaching is discussion. Discussions are usually presented to share the arguments and views of students on religion and science. The presence of religion and science in learning also helps educators add value to the learning process.